A rare case of Sjögren’s syndrome in pregnancy and its perinatal outcome- Fetal congenital heart block - Kapoor, Shavika; Shah, Sangeeta; Mitra, Mrinalini (Indian Journal of Case Reports, 2025)
Sjögren’s syndrome is an autoimmune disease that commonly affects women after the fourth decade of life. Management of pregnancy in women with Sjögren’s syndrome poses unique challenges due to potential maternal and fetal complications. Children born to women with Sjögren’s syndrome can have a higher incidence of prematurity, low birth weight, hypoxic-ischemic encephalopathy, and congenital heart block. We describe the case of 24-year-old primi at 36 weeks of gestation with Sjögren’s syndrome and hypothyroidism, resulting in congenital heart block in the fetus. In this case report, we will discuss the management and perinatal outcome of pregnancy in the case of Sjögren’s syndrome.